Oxidative Stress in Parasitic Diseases-Reactive Oxygen Species as Mediators of Interactions between the Host and the Parasites - Marta Pawłowska; Celestyna Mila-Kierzenkowska; Jan Szczegielniak; Alina Woźniak (MDPI AG, 2023)
Oxidative stress plays a significant role in the development and course of parasitic infections, both in the attacked host organism and the parasite organism struggling to survive. The host uses large amounts of reactive oxygen species (ROS), mainly superoxide anion (O2•−) and hydrogen peroxide (H2O2), to fight the developing parasitic disease. On the other hand, the parasite develops the most effective defense mechanisms and resistance to the effects of ROS and strives to survive in the host organism it has colonized, using the resources and living environment available for its development and causing the host's weakening. The paper reviews the literature on the role of oxidative stress in parasitic diseases, which are the most critical epidemiological problem worldwide. The most common parasitosis in the world is malaria, with 300-500 million new cases and about 1 million deaths reported annually. In Europe and Poland, the essential problem is intestinal parasites. Due to a parasitic infection, the concentration of antioxidants in the host decreases, and the concentration of products of cellular components oxidation increases. In response to the increased number of reactive oxygen species attacking it, the parasites have developed effective defense mechanisms, including primarily the action of antioxidant enzymes, especially superoxide dismutase and nicotinamide adenine dinucleotide phosphate hydrogen (NADPH)-dependent complexes glutathione and thioredoxin.